GIS-MCDA Based Land Capability Analysis for Sustainable Food Production in the Kurdistan Region of Iraq - Nasir, Salam Mahmood; Kamran, Khalil Valizadeh; Blaschke, Thomas; Karimzadeh, Sadra (Iraqi Journal of Science, 2026)
Food production is vital to global food security, entailing significant social, economic, and environmental implications. The Kurdistan Region of Iraq (KRI) possesses abundant natural and human resources essential for agriculture, including extensive agricultural land, water resources, and a favorable climate. However, challenges such as population growth, displacement of large numbers of residents from other provinces to the Kurdistan Region, unplanned urban expansion encroaching on agricultural areas, useless land accumulation, and agricultural land degradation pose substantial threats to sustainable food production (SFP). The study's primary objective is to assess and map the potential for SFP in the region, enabling stakeholders to formulate strategies for sustainability and ensure food security. The methodology involved classifying land capability using Geographic Information System - Multi-Criteria Decision Analysis GIS-MCDA approaches, including the fuzzy analytical hierarchy process-hybrid model (F-AHP) and fuzzy analytical network process F-ANP. The dataset encompassed variables related to land capability for food production, categorized into six main groups: topography, climate elements, water resources, land use-landcover (LULC), geology, and soil characteristics, each with about eighteen sub-factors. Results from F-AHP and F-ANP indicated consistent findings across factor weights and land capability classifications in KRI, showing no significant disparities. Only 10.72% of the region's total land 4245.7 km2 exhibited high capability, while 28.68%, 11355 km2, 34.18%, 13534 km2, and 18.1%, 7168 km2, were moderately capable, low capability, and limited capable land, respectively. An 8.32%, 3295.4 km2 of Kurdistan's land was deemed unsuitable for SFP. The study's insights are crucial for experts, planners, governments, and stakeholders, facilitating the assessment of current food production. Based on these findings, appropriate plans and strategies can be developed to uphold long-term food security in the Kurdistan region.